The procedure for performing parametric equalization of a triangulation grid using Microsoft Excel (The Peerian Journal, 2022)
One of the main tools in the Microsoft Office 2010 package is a spreadsheet program Microsoft Excel, which is part of the software of modern computers. Microsoft Excel is designed for the preparation and mathematical processing of spreadsheets under the control of the Windows operating system. We aim to perform the process of equalization of the triangulation node by the parametric method using Microsoft Excel.